Surgical treatment for diffused-type giant cell tumor (pigmented villonodular synovitis) about the ankle joint - Li, Xingchen (BMC Musculoskelet Disord, 2017)
BACKGROUND: Diffused-type giant cell tumor(Dt-GCT) is a rare, aggressive disorder of the joint synovium, bursa and tendon sheaths. Osseous erosions and subchondral cysts may develop as the result of synovium infiltration in Dt-GCT. We present a retrospective study of a series of patients who are diagnosed with Dt-GCT about the ankle joint, there clinical outcome is evaluated in this study. MATERIAL AND METHOD: Fifteen patients with radiologically and histologically confirmed Dt-GCT about the ankle joint were identified in our foot and ankle department. Patients were managed with open synovectomy for the tumor tissue and bone grafting for bony erosions. X-rays and MRI scans were used for evaluation of the tumor and bony erosions pre- and post-operatively. Pre- and post-operative ankle function was assessed using the American Orthopedic Foot and Ankle Society –Ankle and Hindfoot (AOFAS-AH) score and the Muscularskeletal Tumor Society (MSTS) score. RESULTS: The mean follow-up duration was 37.4 months (range 25 to 50 months). There were 6 males and 9 females, with a mean age of 35 years old (range 18 to 65 years). All patients had talar erosion with the average size of 10.1*9.1*8.2 mm, distal tibia was affected in 5 patients with the average size of 6.2*5.6*5.8 mm. 7 patients had tendon involvement, 2 patients had recurrence and progression of ankle osteoarthritis. Both of them underwent ankle fusion. At the time of last follow-up, the mean AOFAS-AH score increased from 49 to 80 points (p < 0.05), the MSTS score increased from 12 to 22 points (p < 0.05). CONCLUSION: For Dt-GCT with bony erosions, open synovectomy combined with bone grafting seems to be a safe and effective operation for the salvage of ankle joint. Fusion is recommended for failed and severe cartilage destruction of the ankle joint.